(untitled) (IUS LAW Journal, 2025)
The focus of this article is the position of declaratory lawsuits in Civil law procedure in the legislation of Bosnia and Herzegovina. Compared to other types of lawsuits (condemnatory and constitutive), a declaratory lawsuit is primarily aimed at obtainin g a declaration by a court of the existence or non existence of certain legal relationships or rights and the declaration of authenticity of some private or public legal document as well as the determination of a violation of personal rights. Further uses of declarative lawsuit can be, as foreseen by specific legal provisions, a declaration of the existence or non existence of certain facts on which the fulfilment of other rights may depend. The existence of legal interest is one of the procedural elements of a declaratory lawsuit. The use of declaratory lawsuits has proven itself to be a more adequate way of legal protection in certain cases, especially when the use of other types of lawsuits is unavailable for legal or factual reasons. Even though the use of declaratory lawsuits has expanded, the removal of certain restrictions on the right use of declaratory lawsuits could be recommended de lege ferenda in order to facilitate the maximization of the potential of the declaratory lawsuit in civil legal proceedings.